Transcriptomic and metabolomic profile changes in the liver of Sprague Dawley rat offspring after maternal PFOS exposure during gestation and lactation - Ruiyuan Zhang; Guoqi Yu; Tingyu Luo; Xiaojing Zeng; Yan Sun; Bo Huang; Yongjie Liu; Jun Zhang (Ecotoxicology and Environmental Safety, 2024)
Epidemiological and experimental research has indicated an association between perfluorooctane sulfonate (PFOS) exposure and liver disease. However, the potential hepatotoxic effects and mechanisms of low-level prenatal PFOS exposure in offspring remain ambiguous. The objective of this research was to examine the alterations in liver transcriptomic and metabolomic profiles in offspring rats at postnatal day (PND) 30 following gestational and lactational exposure to PFOS (from gestational day 1 to 20 and PND 1 to 21). Pregnant Sprague-Dawley rats were separated into a control group (3% starch gel solution, oral gavage) and a PFOS exposure group (0.03 mg/kg body weight per day, oral gavage). Histopathological changes in liver sections were observed by hematoxylin and eosin staining. Biochemical analysis was conducted to evaluate changes in glucose and lipid metabolism. Transcriptomic and metabolomic analyses were utilized to identify significant genes and metabolites associated with alterations of liver glucose and lipid metabolism through an integrated multi-omics analysis. No significant differences were found in the measured biochemical parameters. In total, 167 significant differentially expressed genes (DEGs) related to processes such as steroid biosynthesis, PPAR signaling pathway, and fat digestion and absorption were identified in offspring rats in the PFOS exposure group. Ninety-five altered metabolites were exhibited in the PFOS exposure group, such as heptaethylene glycol, lysoPE (0:0/18:0), lucidenic acid K, and p-Cresol sulfate. DEGs associated with steroid biosynthesis, PPAR signaling pathway, fat digestion and absorption were significantly upregulated in the PFOS exposure group (P < 0.05). The analysis of correlations indicated that there was a significant inverse correlation between all identified differential metabolites and the levels of fasting blood glucose, high-density lipoprotein, and triglycerides in the PFOS exposure group (P < 0.05). Our findings demystify that early-life PFOS exposure can lead to alterations in transcriptomic and metabolomic profiles in the offspring’s liver, which provided mechanistic insights into the potential hepatotoxicity and developmental toxicity associated with environmentally relevant levels of PFOS exposure.